Anticancer potential of aminomethylidene-diazinanes I. Synthesis of arylaminomethylidene of diazinetriones and its cytotoxic effects tested in glioblastoma cells. Issue 19 (1st October 2017) - Pianovich, Nichole A.; Dean, Mathew; Lassak, Adam; Reiss, Krzysztof; Jursic, Branko S.
Graphical abstract: Abstract: Diazinane and aryl moieties with vinylamine linkers were synthesized to investigate the importance of their structural variations as potential anti-glioblastoma agents. Structural variations incorporated on to the diazinane moiety included oxa and thio derivatives, each with a variety of nitrogen-bound substituents. The size and shape of the aromatic moiety was varied, with the final variation introducing two carbonyl groups, yielding a substituted anthraquinone. Readily available diazinanes and aryl amines were used as an advantageous foundation. Several parameters were calculated whilst engineering these compounds, including: C log P, molecular polarizability, polar surface area, minimal molecular projected area, and pKa . In addition, a simple and efficient procedure was developed to synthesize these compounds. It was demonstrated that a vinylamine with 1, 3-diazinane-2, 4, 6-trione and 1-anthraquinone moiety is the most promising drug candidate causing almost 70% of LN229 tumor cell death at 1 µg/ml. In addition, its molecular polarizability, polar surface area and minimal molecular projected area indicate a possible potential of this molecule for crossing BBB.